Practical Guide to the Management of Acute and Chronic Pain in the Presence of Drug Tolerance for the Healthcare Practitioner - Vadivelu, Nalini (the Academic Division of Ochsner Clinic Foundation, 2014)
BACKGROUND: Drug tolerance has been on the rise in recent years worldwide, and consequently, pain management in our population has become challenging. METHODS: Discussed in this review are commonly abused drugs and considerations for treating acute and chronic pain states in patients with substance disorders. RESULTS: After marijuana, alcohol, and tobacco, the most widely abused substances are oxycodone (Oxycontin), diazepam (Valium), and methylphenidate (Ritalin). Urine testing can detect metabolites of drugs used by patients and is useful for assessing drug abuse, medication diversion, and drug interactions. The comprehensive treatment of pain in a patient with addictive disorder or tolerance must address 3 issues: the patient's addiction, any associated psychiatric conditions, and the patient's pain. Eliciting a detailed history of drug abuse—illicit drugs as well as prescription drugs—and ascertaining if the patient is currently enrolled in a methadone maintenance program for the treatment of drug addiction is vital. CONCLUSION: Medical observation, supportive care, multidisciplinary pain management, and timely interventions as necessary are the keys to safe outcomes in these patients.